Biochemical Indicators for Resistance Against Rhizoctonia Root Rot in Soybean (Journal of Plant Disease Sciences, 2018)
Biochemical characterization of soybean cultivars was carried out against Rhizoctonia root rot disease. Study showed significant correlation of disease resistance with biochemical parameters. In absolutely resistant cultivar AMS-1002 total soluble sugar was 5.47 (mg/g fresh wt.) in healthy root sample, which increased up to 5.52 (mg/g fresh wt.) after pathogen inoculation whereas in highly susceptible cultivar TAMS-38 it was 3.64 (mg/g fresh wt.) in healthy root sample but due to infection of pathogen which decreased up to 3.63 (mg/g fresh wt.). Highest concentrations of total phenols were observed in genotypes AMS-1002, AMS-103, AMS-3923 and MAUS-71. Also, AMS 1002 and AMS-103 showed peroxidase content of 14.64 (units/min/g fresh wt.) and 11.50 (units/ min/g fresh wt.) in healthy root, which increased up to 17.40 (units/min/g fresh wt.) and 13.96 (units/ min/g fresh wt.) in infected root. PPO activity ranged from 1.72 units/min/g fresh wt. for genotype MAUS-71 to 4.22 units/min/g fresh wt. for AMS-1002. PAL increased significantly in infected tissues of AMS-1002, AMS-103, AMS-3923 and MAUS-71 genotypes compared to the healthy tissues. Higher phenols, total and reducing sugars content in cultivars coupled with other biochemical components might play a vital role in providing resistance towards root rot in soybean.
Keywords: Rhizoctonia root rot; Soybean; Polyphenol oxidase; Peroxidase; ammonia-lyase